Peculiarities of Sentencing Persons with Mental Disorders That Do Not Exclude Mental Disorders - Mamajanov Abrorbek Mirabdullaevich (International Journal of Law And Criminology, 2025)
In our republic, attention has been paid to establishing responsibility for the commission of crimes by persons with mental disorders, bringing it in line with international standards, and a number of measures have been taken to overcome the legal gap and contradictions that hinder the effective protection of citizens' rights and freedoms. In this regard, early detection and diagnosis of mental disorders, improving the quality of treatment for people with mental disorders and the consistent continuation of the policy of improving criminal legislation, the widespread introduction of the humanistic principle into criminal penalties and their enforcement system are identified among the priorities for the development of the judicial and legal sphere, and research in this area is becoming increasingly important.